2022
DOI: 10.2147/nss.s370471
|View full text |Cite
|
Sign up to set email alerts
|

Independent Association Between Oxygen Desaturation Index and Cardiovascular Disease in Non-Sleepy Sleep-Disordered Breathing Subtype: A Chinese Community-Based Study

Abstract: Purpose Non-sleepy sleep-disordered breathing (SDB) is increasingly recognized as an important clinical subtype. The association between non-sleepy SDB and cardiovascular disease (CVD) is not well understood. Our objectives were to investigate the relationship between non-sleepy SDB and CVD and determine which nocturnal hypoxia parameter most strongly reflects this association in a large community population. Patients and Methods Cross-sectional data from 3626 randomly-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…There were multiple studies showing that ODI was a more sensitive and valuable predictor to OSA 41,42 which was consistent with our results. Oxygen desaturation parameters were better markers for cardiovascular disease 43 and OSA associated morbidity and mortality compared to the AHI. 44,45 In turn, it was reported that BMI influences the accuracy of ODI for OSA diagnosis.…”
Section: Discussionmentioning
confidence: 89%
“…There were multiple studies showing that ODI was a more sensitive and valuable predictor to OSA 41,42 which was consistent with our results. Oxygen desaturation parameters were better markers for cardiovascular disease 43 and OSA associated morbidity and mortality compared to the AHI. 44,45 In turn, it was reported that BMI influences the accuracy of ODI for OSA diagnosis.…”
Section: Discussionmentioning
confidence: 89%
“…Time below 90% saturation (T90) is recognised as an independent predictor of allcause CVD mortality and widely used in many studies [4,[23][24][25][26][27]. The calculation method of T90 varies among studies and can be divided into time-based and percentage-based parameters, as shown in Table 1 [4,14,18,22,27,28]. The time-based TST90 measures the time per night with oxygen saturation below 90%, and thus measures the cumulative hypoxemia insult.…”
Section: Time Below 90% Saturationmentioning
confidence: 99%
“…Percentage-based parameter T90% [18] The percentage of sleep time with oxygen saturation level below 90%. The unit of this parameter is %.…”
Section: Time Below 90% Saturationmentioning
confidence: 99%
See 2 more Smart Citations